Effective tax rates under IP tax planning - Lisa Evers; Christoph Spengel (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
Tax planning with intangibles has become one of the most popular and most vividly debated topics in international taxation. We incorporate various intellectual property (IP) tax planning models into forward-looking measures of effective tax rates, namely the disposal of intangibles to low-tax subsidiaries, intra-group licensing arrangements, and intra-group contract R&D. In doing so, we draw upon the methodology put forward by Devereux and Griffith and amend this model by considering a research & development (R&D) investment which is carried out by a parent company, whereby the resulting intangible is exploited by a foreign subsidiary. We point out analytically under which conditions IP tax planning achieves the objective of reducing the effective average tax rate of the group. We find that the disposal of intangibles to low-tax subsidiaries does not achieve this tax planning objective, if the true value of the asset is subject to tax upon the disposal. We show to what extent the parent must understate the value of the intangible in order to reduce the group's tax burden. We furthermore point out that contract R&D may generally achieve a significant lower effective tax burden. We present cost of capital and effect average tax rates to illustrate these findings.
urn:nbn:de:bsz:180-madoc-374564
Keywords: F23; H25; H32; H87; K34; 330; corporate taxation; effective tax rate; tax planning; profit shifting; transfer pricing; intellectual property; intangible assets; contract R&D